A novel and efficient one-pot strategy for the synthesis of 1, 2, 4-triazoles: access to synthesis of penipanoid A and its analogues. Issue 4 (18th January 2023) - Reddy, A. Satyanarayana; Reddy, V. Krishna; Rao, G. Nageswara; Basavaiah, K.; Nagulapalli Venkata, Kalyan C.
Abstract : We developed a novel one-pot strategy for synthesizing biologically important 1, 2, 4-triazole motifs from easily accessible 4-hydroxy phenylacetic acid, formamidine hydrochloride and hydrazine derivatives under mild conditions. Abstract : We developed a novel one-pot strategy for synthesizing biologically important 1, 2, 4-triazole motifs from easily accessible 4-hydroxy phenylacetic acid, formamidine hydrochloride and hydrazine derivatives under mild conditions. This strategy enabled us to synthesize the natural penipanoid A and its analogues in one step.